2009
DOI: 10.18806/tesl.v26i2.413
|View full text |Cite
|
Sign up to set email alerts
|

Early Language and Literacy Development Among Young English Language Learners: Preliminary Insights from a Longitudinal Study

Abstract: This article reports on the preliminary findings of a two-staged empirical study aimed at gaining insights into the variables salient in the early language and literacy development of young English language learners (ELL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
2
24
0
2
Order By: Relevance
“…Words that are beyond level 10 are registered as 'Off-list' words. A validation study of this reference corpus (Roessingh & Elgie, 2009) and the lexical profiling strategy that underlies the online tool confirms for us the utility of both this tool and the approach to language sample analysis it affords for the purposes of our research reported here. It appears that patterns in children's vocabulary development remain remarkably stable over time (Biemiller & Slonim, 2001), and although they may acquire different content words (tiddly winks has turned into warrior games) the general, high utility academic words that are characteristic of CALP-like discourse have not changed.…”
Section: Assessment Of Early Literacysupporting
confidence: 71%
“…Words that are beyond level 10 are registered as 'Off-list' words. A validation study of this reference corpus (Roessingh & Elgie, 2009) and the lexical profiling strategy that underlies the online tool confirms for us the utility of both this tool and the approach to language sample analysis it affords for the purposes of our research reported here. It appears that patterns in children's vocabulary development remain remarkably stable over time (Biemiller & Slonim, 2001), and although they may acquire different content words (tiddly winks has turned into warrior games) the general, high utility academic words that are characteristic of CALP-like discourse have not changed.…”
Section: Assessment Of Early Literacysupporting
confidence: 71%
“…The development of academic literacy is a gradual, complex, and protracted process that extends into the adult years and postsecondary education (Ravid & Tolchinsky, 2002;Roessingh & Elgie, 2009). This development occurs through access to a large (and continually increasing) reservoir of linguistic resources that an individual can flexibly and efficiently mobilize and manipulate for diverse communicative and academic purposes, principally through written mode.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that strong academic language skills in one's native language are associated with successful second language learning and academic achievement (Thomas & Collier, 2002). Furthermore, researchers have emphasized that children's literacy skills in their first language transfer to a second language (Cummins, 2000;Roessingh & Elgie, 2009). Our data indicate that insight into a child's native language learning is also meaningful for generating an overall understanding of a child's risk and protective factors related to their social and emotional development and academic learning in school.…”
Section: Study Imentioning
confidence: 57%
“…More research is warranted to design and administer psychometrically sound measures that can be used with general populations of students as a means of providing early, cost-effective screening for behaviours indicative of social, emotional, and academic risk or weakness, and for identifying social, emotional, and academic behaviour patterns. Finally, existing classroom-based measures administered to all students do not provide insight into a child's proficiency in the dominant language in school and/or in their home language, which may have an impact on the student's social, emotional, and academic success (Cummins, 2000;Roessingh, 2004;Roessingh & Elgie, 2009).…”
Section: Past Researchmentioning
confidence: 99%